Curricular and pedagogic innovation in a Social Education programme: findings from the implementation of PBL - Fernandes, Sandra (2020)
This paper describes the results from the implementation of PBL experiences in the Social Education degree programme at Portucalense University, Portugal. It aims to discuss the curricular and pedagogical changes implemented in the past three years, in this programme. In total, five PBL experiences will be reported in this study: three editions were carried out with second year students and two editions with first year students, since the academic year of 2017/2018 to 2019/2020. The objective of this study is to report findings concerning the main curricular and pedagogic innovations implemented as a result of the shift to the PBL approach, such as the teaching strategies, assessment methods, learning outcomes, student competences, partnerships with community, amongst others. Student's and Teacher's opinions have been collected at the end of each PBL edition, through questionnaires and individual narratives. Until the present, ten different curricular units have participated in the PBL projects, involving about forty students and five teachers in the five PBL editions mentioned. The results, in general, suggest a positive view of the PBL experiences and the role of the project to enhance student centred teaching and learning. Teachers showed interest in developing active learning strategies and openness to change / rethink their teaching practices. Creativity, oral and written communication, problem solving, project management, interpersonal and teamwork skills were key competencies highlighted by students as a result of the PBL project. This also resulted in greater student autonomy and the development of an active role by students, characteristics which are in accordance with the main guidelines of European Standards and Guidelines for Quality in Higher Education.